Pengaruh Brand Ambassador Soong Jong Ki dan Kualitas Produk Terhadap Keputusan Pembelian Skincare Scarlett (Studi Kasus pada Mahasiswa Manajemen Unisma Angkatan 2019) - Faradina Rochmawati Ningrum; Nur Hidayati; Andi Normala (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this study was to determine the effect of brand ambassadors and product quality on purchasing decisions. The sample used in this study were 86 respondents who were Unisma Management Students Batch 2019 users of Scarlet skincare. Data collection techniques using a questionnaire. The analytical method used is multiple linear regression analysis using SPSS 16.0 computer software for data processing. The results of this study indicate that brand ambassadors, product quality has a significant positive affects purchasing decisions. Keywords: Brand Ambassador, Product Quality and Purchase Decision.